Prognostication of Heart Failure Evolution: From Circulating Biomarkers to Genetic Risk Predictive Score - Berezin, A. E.; Peterlin, B.; Lichtenauer, M.; Mozos, I.; Березін, Олександр Євгенійович (My University, 2021)
Circulating protein-based biomarkers are well-established tools for the diagnosis, stratification, and management of heart failure. Despite having a certain difference in biomarker panels that are recommended by the American Heart Association/American College of Cardiology and European Cardiology Society to routine clinical practice, cardiac biomarkers, mainly natriuretic peptides, demonstrate high discriminative ability to rule out the diagnosis of HF, and predict the risk of mortality/hospitalization among patients with overt HF. Although there are several challenges regarding the economic burden with biomarkers, their reproducibility, affordability, and interpretations of the results in serial measures, biomarker-based guided HF management, and prediction appear to be promising. However, there is no agreement in the design of various biomarker strategies (single vs. multiple biomarker panel, peak or serial measures, protein-based vs. transcriptomics-based biomarkers, and genetic scores vs. circulating biomarker scores), which could best fitted to each phenotype of HF and provide strong evidence for personified therapy of HF. We included four articles in the special issue “Prognostication of Heart Failure Evolution: From Circulating Biomarkers to Genetic Risk Predictive Score,” and these will be attractive for readers who are interesting in this topic.
Keywords: heart failure; biomarkers; stratification; prediction; risk scores